Laporan Kasus : Pemeriksaan Forensik dan Aspek Medikolegal Pada Kasus Kematian Akibat Kecelakaan Kerja - Patimah Sri Ayu Bijak Lestari Assagaf; Mauluddin Mauluddin; Denny Mathius; S. Zulfikar Assegaf (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: The phenomenon of accidents and illnesses in the workplace has killed and claimed many victims. Every work activity carried out always contains a risk of failure, whether resulting from inadequate planning, inaccurate implementation, or risks that can never be predicted due to weather conditions, natural disasters, and others. One of the risks that often occurs at work is work accidents. The most common reason for accidental deaths in industrial workplaces is a lack of awareness and safety precautions when using machine tools that have the potential to result in fatal injuries. Case Description: We report a case of death due to a work accident, involving a 25 year old man, where the victim fell into the spice kneading machine while trying to pick up a fallen rag, so the victim's hand got caught in the blade of the machine, then the victim fell into the spice kneading machine. Various injuries were found including bruises, abrasions, lacerations, open wounds and fractures to the ribs. Fractures of the ribs indicate a high energy trauma mechanism. Apart from that, cyanosis was found on the lips, fingers and toes, which indicates respiratory failure due to traumatic asphyxia. Conclusion: Cases of death due to workplace accidents are often reported. Forensic and medicolegal examinations in this case can help determine the mechanism and cause of death. Workplace accidents usually occur due to workers' carelessness, lack of use of personal protective equipment, as well as lack of knowledge of potential or hazards that can occur in the workplace.